Implementing a method based on near infrared spectroscopy for the "in-situ" determination of ammonia/water composition in an absorber test bench. Issue 3 (September 2016) - Barba, M. Isabel; Berdasco, Miguel; Salavera, Daniel; Larrechi, M. Soledad; Coronas, Alberto
Abstract: This study presents the first results of composition measurement in an ammonia/water mixture determined at real time using near-infrared (NIR) spectroscopy in an absorber test bench. Two cells were designed and constructed; a static cell for calibrating and a dynamic cell for measuring in the absorber test bench. The ammonia absorption band was not significantly affected by the solution flow rate and neither by small variations in the temperature and pressure. A linear regression model between the absorbance value at 1033 nm and the ammonia concentration was established. This model was used to estimate the concentration in an ammonia/water absorber test bench. The methodology was validated by density measurements of the samples. The value of the mean deviation was 0.0024.